Effects of Hypericum perforatum on the healing of xenografts: a histomorphometric study in rabbits. Issue 4 (May 2017) - Damlar, İ. and Arpağ, O.F. and Tatli, U. and Altan, A.
Abstract: The aim of this study was to investigate effects of the Hypericum perforatum (St John's Wort) on bone healing in rabbit calvarium. Ten male New Zealand rabbits each had three bicortical defects made in the calvarial bones, which were filled with xenograft, xenograft + H perforatum oil extract, and autogenous graft. Four weeks postoperatively all rabbits were killed and the bony defects examined histomorphometrically. Tissue compartments including new bone (p < 0.001), marrow space (p < 0.001), and residual bone grafts (p = 0.014) differed significantly among groups. The volume of residual graft was significantly decreased in the xenograft/ H perforatum group compared with those with xenografts alone (p = 0.0147). The differences in microarchitectural variables of de novo bone formation were also significant (trabecular thickness (p < 0.001), trabecular width (p < 0.001), trabecular separation (p = 0.001). There were no significant differences in node:terminus ratio between the xenograft/ H perforatum group and the other two groups. However, the difference in node:terminus ratio between the autogenous graft and xenograft group was significant (p = 0.001) Oil extracts of H perforatum improved bony healing in defects filled with bovine-derived xenografts.